2007
DOI: 10.1162/coli.2007.33.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Generating Referring Expressions: Making Referents Easy to Identify

Abstract: It is often desirable that referring expressions be chosen in such a way that their referents are easy to identify. This article focuses on referring expressions in hierarchically structured domains, exploring the hypothesis that referring expressions can be improved by including logically redundant information in them if this leads to a significant reduction in the amount of search that is needed to identify the referent. Generation algorithms are presented that implement this idea by including logically redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 13 publications
5
89
0
Order By: Relevance
“…Redundancy has been used in cartographic research before, especially for generation of route directions [54,55]. In order to test the effect of redundancy on the perception of changes on the animated map, we designed three additional maps.…”
Section: Visual Variables and Cartographic Redundancymentioning
confidence: 99%
“…Redundancy has been used in cartographic research before, especially for generation of route directions [54,55]. In order to test the effect of redundancy on the perception of changes on the animated map, we designed three additional maps.…”
Section: Visual Variables and Cartographic Redundancymentioning
confidence: 99%
“…For example, Paraboni, van Deemter, and Masthoff (2007) found that overspecification increases in spatially complex domains, while Arts (2004) for an apartment, a speaker may refer to an object currently in focus using ostensibly redundant properties in order to confirm that she has understood and accepted her partner's previous utterance.…”
Section: Conceptualisation: Determining the Content Of Referential Npsmentioning
confidence: 99%
“…Paraboni and van Deemter (2013) focus on reference in spatial and hierarchical domains (e.g. a document divided into sections and subsections), where overspecification has been found to facilitate identification of a referent to a degree that is not predicted by standard reg algorithms (Paraboni et al, 2007). Their new findings, which are incorporated in a new algorithm, suggest that overspecification plays a facilitative role for a listener under conditions where finding a path through a space may be problematic.…”
Section: Conceptualisation: Determining the Content Of Referential Npsmentioning
confidence: 99%
“…This is supported by evidence from Mangold and Pobel (1988), who found that overspecification shortened identification time if the redundant feature was better perceptible than the discriminating feature. The utility (and thus incidence) of this type of overinformativeness may be increased when contexts are complex or otherwise demanding (Paraboni et al 2007), and the cooperative speaker may be motivated to reduce the search space Brought to you by | De Gruyter / TCS Authenticated Download Date | 5/9/16 9:58 PM for the hearer. Arts (2004Arts ( , 2011 found that certain types of overspecification almost consistently led to accelerated resolution, especially attributes concerning the location of an object.…”
Section:  Hearer-oriented Reasons For Overinforming  Facilitationmentioning
confidence: 99%
“…Computational linguistic research has documented high rates of overinforming in human speech (Dale & Reiter 1995;Viethen & Dale 2006;Paraboni et al 2007;van der Sluis & Krahmer 2007;). This dialogue between psycholinguistics and computational linguists has been mutually beneficial: 1 how speakers choose the content and form of their REs is not only of interest to psycholinguists and philosophers of language, it is a pervasive challenge for natural language generation systems.…”
Section:  Applications Of Research Into Overspecificationmentioning
confidence: 99%